Endoglycan (PODXL2) is proteolytically processed by ADAM10 (a disintegrin and metalloprotease 10) and controls neurite branching in primary neurons. Issue 9 (14th August 2021) - Hsia, Hung‐En; Tüshaus, Johanna; Feng, Xiao; Hofmann, Laura I.; Wefers, Benedikt; Marciano, Denise K.; Wurst, Wolfgang; Lichtenthaler, Stefan F.
Abstract: Cell adhesion is tightly controlled in multicellular organisms, for example, through proteolytic ectodomain shedding of the adhesion‐mediating cell surface transmembrane proteins. In the brain, shedding of cell adhesion proteins is required for nervous system development and function, but the shedding of only a few adhesion proteins has been studied in detail in the mammalian brain. One such adhesion protein is the transmembrane protein endoglycan (PODXL2), which belongs to the CD34‐family of highly glycosylated sialomucins. Here, we demonstrate that endoglycan is broadly expressed in the developing mouse brains and is proteolytically shed in vitro in mouse neurons and in vivo in mouse brains. Endoglycan shedding in primary neurons was mediated by the transmembrane protease a disintegrin and metalloprotease 10 (ADAM10), but not by its homolog ADAM17. Functionally, endoglycan deficiency reduced the branching of neurites extending from primary neurons in vitro, whereas deletion of ADAM10 had the opposite effect and increased neurite branching. Taken together, our study discovers a function for endoglycan in neurite branching, establishes endoglycan as an ADAM10 substrate and suggests that ADAM10 cleavage of endoglycan may contribute to neurite branching.